Are Price-Based Capital Account Regulations Effective in Developing Countries? - David, Antonio C. (World Bank, Washington, DC, 2012)
The author evaluates the effectiveness of policy measures adopted by Chile and Colombia, aiming to mitigate the deleterious effects of pro-cyclical capital flows. In the case of Chile, according to his Generalized Method of Moments (GMM) analysis, capital controls succeeded in reducing net short-term capital flows but did not affect long-term flows. As far as Colombia is concerned, the regulations were capable of affecting total flows and also long-term ones. In addition, the co-integration models indicate that the regulations did not have a direct effect on the real exchange rate in the Chilean case. Nonetheless, the model used for Colombia did detect a direct impact of the capital controls on the real exchange rate. Therefore, the results do not seem to support the idea that those regulations were easily evaded.